Manajemen Pembelajaran Pada Masa Pandemi Madrasah Mu’allimin Muhammadiyah Yogyakarta - Syaifullah K Boli; Dian Hidayati; Didit Haryadi (Journal of Education and Teaching (JET), 2022)
There are differences in learning management carried out by teachers when the pandemic conditions hit. During the pandemic, madrasa teachers carry out online-based learning management. Therefore, this evaluation study aims to evaluate teacher learning management. The research subjects were teachers of the Muhammadiyah Yogyakarta Madrasah Mu'allimin, totaling 35 people. Data collection techniques in the form of questionnaires (Likert scale 1 – 4) and interviews. The data analysis technique used is quantitative descriptive using descriptive analysis. Based on the results of research on learning management at Madrasah Mu'allimin Muhammadiyah Yogyakarta, it can be concluded that the components of learning management (1) Planning get a percentage with a very good category of 83% (2) Organizations get a percentage of 88% with a very good category (3) Motivation gets a percentage 88% with very good category and (4) Evaluation gets a percentage of 84%. Overall of the applied Management functions.